Il trattamento dei nomi propri nella traduzione di documenti giuridici tra l’italiano e l’inglese [The translation of proper names from Italian to English in legal documents] - Loiacono, Rocco (Department of Interdisciplinary Studies in Translation, Languages and Culture of the University of Bologna, Italy, 2011)
International treatiesw have been defined as "hybrid texts", that is, texts that are produced outside the setting of the legal systems of the interested States. This does not mean, however, that their translation will be free from problems of an intervcultural nature. That is, some form of mediation between the legal cultures of the signatory States will be required. The corpus of documents chosen for analysis in this paper is the bilateral treaties that are in force between Italy and Australia. These two countries belong to different legal cultures: Italy to that of continental civil law and Australia to that of the common law. In translating legal documents in this setting, difficulties will arise as there can never be a perfect correspondence between legal systems. To overcome such difficulties, scholars have suggested that a comparative approach be adopted whereby a translator acquires a good knowledge of the sense and the function of particular legal terms in the source language before undertaking their translation.The traditional definitions of proper names and common nouns have been reviewed in recent times, in particular from the point of view that proper names have a sense which is derived from a particular cultural situation. This theory posits that words of expressions previously not considered to be proper names can now be potentially viewed as such. As legal terms are inextricably linked to the culture in which they have developed, each legal term has a specific reference that derives from the legal culture to which it belongs, it may be argued that legal terms can be considered as belonging to the category of proper names in certain circumstances. Numerous strategies have been applied by translators to proper names that take into account their cultural significance and meaning in order to render them appropriately in the target language. If legal terms can be classified as proper names, then various strategies that have been developed with regard to the translation of proper names may be applicable to legal translation. This hypothesis will be applied to the corpus of documents the subject of this paper.